2015
DOI: 10.1007/s12098-015-1889-x
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis in Children: Diagnosis and Management

Abstract: Uveitis is a term used to describe inflammation of uvea, which is the middle layer of eye. It is an important cause of blindness in children in both developed and developing countries. Delayed diagnosis, inadequate treatment and risk of amblyopia are some of the factors that are unique to childhood uveitis and are responsible for significant morbidity seen with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…3,21,24,26 Algunos exámenes complementarios importantes son: angiografía retiniana fluoresceínica, útil en uveítis posterior; tomografía de coherencia óptica (OCT), que realiza una imagen óptica de las capas de la retina y ayuda en el manejo del proceso inflamatorio retiniano; ultrasonido ocular, útil en la visualización del segmento posterior, y la angiografía con indocianina verde, para el estudio de la coroides. [27][28][29][30] En caso de los pacientes que inician inmunosupresión, se deben revisar las serologías por hepatitis B y C, ELISA por VIH, además de la PPD y exámenes de heces por parásitos. Se debe revisar el esquema de vacunas; en caso de que esté incompleto, se debe actualizar antes del inicio de la inmunosupresión, si la condición clínica lo permite.…”
Section: Diagnósticounclassified
See 1 more Smart Citation
“…3,21,24,26 Algunos exámenes complementarios importantes son: angiografía retiniana fluoresceínica, útil en uveítis posterior; tomografía de coherencia óptica (OCT), que realiza una imagen óptica de las capas de la retina y ayuda en el manejo del proceso inflamatorio retiniano; ultrasonido ocular, útil en la visualización del segmento posterior, y la angiografía con indocianina verde, para el estudio de la coroides. [27][28][29][30] En caso de los pacientes que inician inmunosupresión, se deben revisar las serologías por hepatitis B y C, ELISA por VIH, además de la PPD y exámenes de heces por parásitos. Se debe revisar el esquema de vacunas; en caso de que esté incompleto, se debe actualizar antes del inicio de la inmunosupresión, si la condición clínica lo permite.…”
Section: Diagnósticounclassified
“…En definitiva, en niños se debe tener especial cuidado con el riesgo de retardo en el crecimiento pondoestatural y el riesgo de osteoporosis. 1,24,28 Para evitar estas complicaciones, se recomienda bajar la dosis al cabo de 4 semanas a menos de 0,15mg/kg y debe restringirse a un máximo de 3 meses. Recientemente, se ha propuesto la utilización de pulsos intravenoso (IV) en vez de su uso vía oral (VO), pero amerita mayores estudios en población pediátrica.…”
Section: Tratamiento Sistémicounclassified
“…Uveitis in children is often discovered as part of a routine eye examination, as many children do not report any symptoms, and this silent, insidious inflammation can be difficult to treat and can lead to further complications if not handled skillfully. 1 It is well established that in a pediatric patient, inflammation and neovascularization of the retina can often coexist. 2 It is less common for children to have a classic presentation of a uveitic disease, and it can be challenging to assess pediatric choroidal neovascularization secondary to an inflammatory insult.…”
mentioning
confidence: 99%
“…Pediatric uveitis 1 is a topic of special interest not only because of the unique diagnostic and therapeutic challenges but also because of the variations in clinical presentation and spectrum. Uveitis in children is often discovered as part of a routine eye examination, as many children do not report any symptoms, and this silent, insidious inflammation can be difficult to treat and can lead to further complications if not handled skillfully.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Data from both clinic-and populationbased surveys have shown that children and adolescents develop ocular inflammation less frequently than adults. 17,18 Children and adolescents with uveitis are more likely to have severe, chronic inflammation however, and therefore tend to be at higher risk of developing ocular complications and permanent vision loss 19,20 consequences that can impact vision-related quality of life and function for many future decades.…”
mentioning
confidence: 99%